Pengembangan Webgis Untuk Menentukan Jalur Aman Dari Kriminal Di Kota Malang Menggunakan Algoritme Bellman-Ford - Cendy Nelasari; Fatwa Ramdani; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang city is one of the big cities in East Java which has experienced a fairly rapid population growth in the last seven years, as one of the big cities Malang City also has problems that are generally owned by other big cities, such as crimes. Malang City is one of the cities in East Java which has a high number of criminal cases with a lot of criminal cases occurring around the highway. One of the solutions that can be done to reduce criminal cases on the highway is to provide information about which areas that are vulnerable and which areas are safe to pass based on previous criminal data. Path searching is one of the ways to present that information. One of the path search algorithm that can be applied is the Bellman-Ford algorithm. From previous studies this algorithm was declared to be inefficient for large amounts of data but quite versatile and this algorithm can calculate negative weights and repeatedly check paths so that no path is missed. This research was conducted to create an information system that can provide safe path information also apply the Bellman-Ford algorithm and see the efficiency of the Bellman-Ford algorithm if applied to cases of searching for safe routes from criminal incidents in Malang City. From this study the results that obtained is the safe path information system that runs well and can be opened on multi platforms and also the complexity analysis results which is the efficiency of the Bellman-Ford algorithm, where in terms of time, the Bellman-Ford algorithm is less efficient because based on the analysis results, the order of growth of the time complexity is so the Bellman-Ford algorithm execution time increases quadratically, but in terms of space, Bellman-Ford is quite efficient because based on the results of the analysis, order of growth from its space complexity is n which means that the use of space increases linearly.